Beyond Gun Control: Mapping Gun Violence Prevention Logics. (February 2022) - McMillan, Jordan; Bernstein, Mary
Most research portrays the gun violence prevention (GVP) movement as predominantly white, dominated by national Washington DC-based policy organizations and recently by white middle-class women seeking stronger gun regulations, overlooking organizing by people in racially oppressed communities. In contrast, we extend the multi-institutional politics approach to social movements to understand how interlocking political, institutional, and cultural systems of domination shape GVP efforts across communities. We develop the concept multisystem logic to analyze the public communications of 10 GVP groups in Connecticut from 2013 to 2018. We identify an intervention logic seeking to interrupt or prevent community gun violence and a gun reform logic promoting change in laws and policies. For gun scholars, our approach makes clear that the GVP movement is not solely focused on policy change but on social change more broadly. We suggest the applicability of our model to a range of social movements.